The Role of Genetic Predisposition for Chronotype in Academic Performance - Francesca Meli (School of Economics, University of Bristol, 2026)
Does chronotype affect academic performance? Chronotype is an expression of a person's circadian rhythm. The combination of its biological variation across individuals with rigid social constraints inevitably results in different degrees of alignment between the biological and the social clock, potentially altering efficiency when performing tasks. Using data from Add Health, which combines official high school transcripts with DNA-based information, this paper examines whether the genetic predisposition for a morning-oriented chronotype affects high school GPA. Exploiting the natural experiment of random genetic inheritance among full siblings, I estimate causal effects. Results indicate that, holding the genetic predisposition for educational attainment fixed, a higher propensity for morningness has a positive and statistically significant impact on high school GPA. Findings suggest that this enhancing effect derives from a closer synchronisation between their biological and the social clocks.
Keywords: I10; I21; J24; J13; I14; 330; chronotype; genetics; polygenic index; academic performance; GPA